2019
DOI: 10.1016/j.jhydrol.2019.124103
|View full text |Cite
|
Sign up to set email alerts
|

Return period of vegetation uprooting by flow

Abstract: Fluvial environments are dynamic systems whose evolution and management are strongly affected by the resilience of riparian vegetation to uprooting by flow. Similarly to other natural phenomena, the interactions between flow, sediment and vegetation uprooting is governed by both the magnitude and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…A number of studies have suggested that species distribution can be predicted by the interaction between disturbance regime and key plant traits. Experiments carried out by Perona and Crouzy 12 (but see also recent modelling studies 20,52 ) showed that the vegetation survival to flood can be predicted by the rooting depth distribution prior the flood, as trait responsible to control plant resistance to scour. Floods would tend to remove individuals with less developed root systems, more vulnerable to uprooting, therefore selecting only individuals having longer uprooting depths.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that species distribution can be predicted by the interaction between disturbance regime and key plant traits. Experiments carried out by Perona and Crouzy 12 (but see also recent modelling studies 20,52 ) showed that the vegetation survival to flood can be predicted by the rooting depth distribution prior the flood, as trait responsible to control plant resistance to scour. Floods would tend to remove individuals with less developed root systems, more vulnerable to uprooting, therefore selecting only individuals having longer uprooting depths.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the reference flow event, we therefore use the mean of all such events obtained analytically from Calvani et al. (2019), Qξ(t)=Q0(ξ)et/τ1 where Q 0 is the mean of all peak events exceeding the threshold ξ , and τ 1 is the integral temporal scale of the reference mean event. The reference mean event (red line in Figure 1c) ceases at Tξ+, which is the up‐crossing period of the signal.…”
Section: Riparian Processes and Model Formulationmentioning
confidence: 99%
“…The blue line represents the bed erosion rate (modified from Calvani et al. (2019)).…”
Section: Riparian Processes and Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) and Calvani, Perona, Zen et al. (2019) considered the dynamics of vegetation and variable flow discharges, mathematically simulated by a Compound Poisson Process. Similarly to Perona et al.…”
Section: Introductionmentioning
confidence: 99%